2016
DOI: 10.4187/respcare.04265
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bronchoscopic Findings and Bronchoalveolar Lavage Fluid Cytology in Early Diagnosis of Ventilator-Associated Pneumonia

Abstract: BACKGROUND: Early diagnosis of ventilator-associated pneumonia (VAP) is necessary to reduce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Forty-three of the studies were cohort studies (38 of which were prospective studies) and one was a secondary analysis of data from a randomised controlled trial (RCT) [ 57 ]. All studies were published between 2008 and 2018 with a wide geographical spread; four studies conducted in the UK [ 41 , 44 , 72 , 74 ], eight in the USA [ 40 , 45 , 47 , 50 , 56 , 62 , 67 , 75 ], seven in France [ 51 , 53 , 55 , 63 , 70 , 73 , 78 ], five in Netherland [ 48 , 61 , 66 , 77 , 79 ], three each in both China [ 52 , 65 , 68 ] and Turkey [ 43 , 46 , 82 ], two each in Egypt [ 49 , 76 ], Brazil [ 54 , 81 ], and Italy [ 71 , 83 ], and eight in other countries [ 42 , 57 60 , 64 , 69 , 80 ]. The median sample size was 180 recruited participants, with the 21 being the lowest [ 58 ] and 2080 being the highest number of participants [ 61 ] (see Tables 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-three of the studies were cohort studies (38 of which were prospective studies) and one was a secondary analysis of data from a randomised controlled trial (RCT) [ 57 ]. All studies were published between 2008 and 2018 with a wide geographical spread; four studies conducted in the UK [ 41 , 44 , 72 , 74 ], eight in the USA [ 40 , 45 , 47 , 50 , 56 , 62 , 67 , 75 ], seven in France [ 51 , 53 , 55 , 63 , 70 , 73 , 78 ], five in Netherland [ 48 , 61 , 66 , 77 , 79 ], three each in both China [ 52 , 65 , 68 ] and Turkey [ 43 , 46 , 82 ], two each in Egypt [ 49 , 76 ], Brazil [ 54 , 81 ], and Italy [ 71 , 83 ], and eight in other countries [ 42 , 57 60 , 64 , 69 , 80 ]. The median sample size was 180 recruited participants, with the 21 being the lowest [ 58 ] and 2080 being the highest number of participants [ 61 ] (see Tables 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…White blood cells count > 12,000 or < 4000 cells/mm 3 and/or c. Purulent tracheobronchial secretions; AND 2. BAL culture > 10 4 CFU/mL and/or significant noncontaminant viral load Sens = 92% Spec = 60% Medford et al [ 72 ] UK 150 62.3 1.5 ETA culture > 10 5 or BAL culture > 10 4 New/progressive CXR infiltrates without other obvious cause in patients mechanically ventilated for more than 4 days in the ICU and at least 2 of the following: temperature ≥ 38 °C or ≤ 35 °C, white cell count ≥ 12 or ≤ 4 × 10 9 /L, purulent tracheobronchial secretions, with increasing oxygen requirements, computed tomography evidence of a rapidly cavitating infiltrate, positive pleural fluid culture and/or histological evidence of neutrophilic alveolitis, bronchiolitis, and consolidation in conjunction with pleural fluid microbiology, CT evidence, and histological evidence BAL Sens = 64.1% Spec = 83.0% ETA Sens = 42.6% Spec = 33.7% Textoris et al [ 78 ] France 77 30.75 NR blood Transcriptome DNA microarray analysis (HuSG9 k) purulent bronchial sputum; body temperature more than 38 °C or less than 36 °C; leukocytes more than 10 × 10 9 /L or less than 4 × 10 9 /L; chest radiograph showing new or progressive infiltrates; BAL culture ≥ 10 4 CFU/mL, or ETA culture ≥ 10 6 CFU/mL Sens = NR Spec = NR Vernikos et al [ 80 ] Greece 54 72 1.3 1) Johansen criteria, 2) Modified CPIS > 6 REF 3) Johansen criteria combined with relative neutrophil count 4) CPIS > 6 combined relative neutrophil count 5) RPDMI a score CDC definition (2015) Johansen criteria Sens = 85.7% Spec = 73.7% Modified CPIS > 6 Sens = 62.9% Spec = 73.7% Johansen criteria combined with relative neutrophil count (20% cut off) Sens = 67.6% Spec = 81.3% CPIS > 6 combined relative neutrophil count (20% cut off) Sens = 47.1% Spec = 81.3% RPDMI score Sens = 94.3% Spec = 84.2% …”
Section: Resultsmentioning
confidence: 99%
“…Luna et al 26 found that the use of the CPIS to detect VAP had yielded 93% sensitivity and 100% specificity in a general population of critically ill patients but not confirmed in other studies. 27–29 At a CPIS with a cutoff of ≥5, Liao et al 30 reported a sensitivity of 95.7% and a low specificity of 53.8% for prediction of VAP, while Vernikos et al 31 found a sensitivity of 94.3% and a specificity of 84.2%.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,17 This study also points out that adequate sputum samples are important for analysis. 18,19 Based on the study by Perotin et al, in 2012, biofilm is supposed to be identified if the sample collection is not from sputum but directly from the tube lumen. This study also revealed that Gram-negative bacteria were the primary cause of VAP, 4 a similar finding to that of our study.…”
Section: Discussionmentioning
confidence: 99%